The Consequences of Letter Grades for Labor Market Outcomes and Student Behavior - Tan, Brandon Joel (Journal of Labor Economics, 2023)
I study the consequences of letter grades serving as coarse measures of academic achievement using university administrative data that record both the letter grade and the precise mark (0–100) received for each course that a given student takes. I exploit a regression discontinuity design with marks as the running variable. I find that receiving a better grade in a single class results in USD 32 greater monthly earnings after graduation, a 1.4% increase. I also find that marginal students who receive a worse grade take significantly easier courses and earn lower grades in future semesters.